Teachers' Strategies and Challenges in Implementing English as a Medium of Instruction in an Billingual Classroom - Tabita, Marsela Nayla; Suharyanto, S (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This study investigates teachers’ strategies and challenges in implementing English as a Medium of Instruction (EMI) in a bilingual class. Althought EMI has gained increasing attention in Indonesia, its implementation at the junior high school, particulary in Islamic Billingual context remains underexplored.Methodology: This qualitative involved three general subject teachers. This study employed a qualitative methodology, triangulating data through interviews, classroom observations, and documentation. We conducted data analysis using Creswell's framework and Miles and Huberman's interactive model, which included data reduction, data presentation, and conclusion formulation.Result: This results indicates that teachers employed a variety of teaching strategies to support content comperehension and language development, including vocabulary structuring, multimodal teaching, peer collaboration, gamification, and selective translanguaging. However, teachers faced significant challenges realted to students varying level of language proficiency and complex subject specific terminology. To address these challenges, teachers implemented differentiated instruction, peer tutoring, and continuous professional development with instituonal support.Applications/Originality/Value: This study contributes to existing EMI research by highlighting implementation practices within an Islamic billingual junior high school context, a environtment rarely examined in previous literature. The findings underscore the importance of adaptive pedagogy, institutional support, and continuous teacher training to ensure sustainable EMI practice and provide implications for policy development and future research.